Study of the modifications of the electric field gradient in hexafluorohafnates of transition metals above room temperature - Taylor, Marcela Andrea (1993)
The temperature dependence above room temperature of the hyperfine quadrupole interactions measured by the time differential perturbed angular correlations technique at hafnium sites in AHfF6·nH2O, with A=Co and Zn andn=6, 4 and 0, is presented. The different steps of the dehydration process are reflected by modifications on the hyperfine quadrupole parameters at increasing temperature. The changes in the electric field gradient as water molecules are lost are interpreted in terms of distortions induced in the [HfF6]2− octahedrons.